A SEMANTIC INTERPRETATION OF THE VALUES OF SHALL IN ECONOMICS ENGLISH AS TARGET LANGUAGE - GOGA-VIGARU, Roxana (Journal of Advanced Research in Law and Economics; Vol 2 No 4 (2011): JARLE, Volume II, Issue 2(4), Winter 2011, 2017)
The aim of this paper is to quantify and analyse the meanings of ‘shall’ in point of deontic and epistemic values in a corpus of economics texts made up of financial issues of the Sectorial Operational Programme Human Resources Development 2007–2013–October 2007: Strategy, Financial Plan, Implementation, and Partnership. Since modal verbs express the speaker’s attitude towards the utterance, it is very interesting to investigate the occurrences of ‘shall’ and analyse its values in the above mentioned corpus.